(untitled) (Latakia University Journal -Biological Sciences Series, 2020)
This study was conducted during the period between 15 July 2018 to 1 July 2019 on (401) individuals of horse mackerel Trachurus trachurus caught from the Syrian marine waters. Samples were collected from Ras Al-Basit and Burg-Islam using local fishing methods (gill nets, purse seines). The qualitative and quantitative compositions of the food elements, its seasonal variations, and the biological features (condition factor, general fullness factor, frequency of occurrence) were studied. The results of the morphometric-meristic characteristics of T. trachurus caught in both studied areas showed that they were asymptotic in length and the males were larger than females, whereas the length–weight relationship was strongly and positively correlated (R2 = 0.89). T.trachurus feeds on a wide spectrum of food, reached up to twenty species belonging to four major groups, namely: (Fish, Crustaceans, Molluscs and Annelida). The fishes had occupied the first order (12 species), and the species Bregmaceros nectabanus was the most abundant ( 363 individuals), followed by crustaceans (7 species; the most frequent one was Athanas neithescens ) while the molluscs and worms were represented by one species each . The results showed also that there were no seasonal qualitative changes in diet composition of T.trachurus, and no significant differences of the biological factors were observed in both study areas.